Compressibility and permeability of solidified dredged marine soils (DMS) with the addition of cement andor waste granular materials (WGM) - Rosman, Mohammad Zawawi; Chan, Chee Ming; Anuar, N. M. (UTHM Publisher, 2018)
Dredged marine soils that obtained from dredging work were characterize as geo-waste, which is prone to be dumped rather than to be reused. This type of soil is high in compressibility and low in load bearing capacity. The engineering properties of this soft soil can be improve via soil solidification method. Cement is the common hydraulic binder used in soil solidification, were found to generate the emission of greenhouse gasses (GHG), particularly carbon dioxide (CO2) which also had affected the earth’s atmosphere. Therefore, there has been an increasing interest in using alternate pozzolanic materials such as waste granular materials (WGM) to fully or partially substituted the use of cement in soil solidification. WGM such as coal bottom ash (BA) and palm oil clinker (POC) were opted due to its pozzolanic properties. Prior to the planning of reclamation work using DMS admixed with conventional and/or alternate pozzolanic materials, the consolidation characteristics of the admixed materials must be acknowledged. Hence, the present study will examine the amount of settlement and coefficient of permeability (k) of DMS treated with cement and/or WGM in laboratory-scale experiments. Samples were prepared in various proportion in order to examine the individual effect of the cement and/or alternate pozzolanic materials on compressibility and permeability. For cement-admixed DMS, sample with 20 % of cement have significantly reduced the settlement than untreated and 10 % cemented DMS. For WGM-admixed DMS, the initial void ratio is low as compared to the untreated DMS due to the rearrangement of soil particles, which is densely packed. For cement-WGM-admixed DMS, samples of 15C50BA and 15C50POC displayed significant settlement reduction than 10C100BA, 10C100POC and untreated samples.